Supercritical water promoted aromatics production using ZSM-5 catalyst. (15th February 2022) - Zaker, Azadeh; Tompsett, Geoffrey A.; Wang, Siwen; Bond, Jesse Q.; Timko, Michael T.
Graphical abstract: Highlights: Dodecane conversion is maximized and coking minimized in systems with 5–15 wt% water. Similar effects are seen for a real petroleum feed. The balance between deactivation and reaction rates explains these observations. Abstract: Supercritical water assisted aromatization (SCWA) using ZSM-5 was examined for conversion of dodecane and an atmospheric distillate into benzene, toluene, ethyl benzene, and xylene (BTEX) products. When compared with observations made in the absence of water, addition of 15 wt% or less water resulted in several benefits, including enhanced dodecane conversion rate, decreased formation of coke and coke precursors, and increased BTEX yields, retention of crystallinity (>90%), and retention of Brønsted acid site (BAS) density (60%). In contrast, addition of ≥ 25 wt% water resulted in reduced dodecane cracking rate, reduced aromatic production, decreased crystallinity (<80%), and reduced BAS retention (10%). The BTEX formation mechanism appears to initiate with aliphatic cracking to produce alkenes, followed by isomerization and cyclization, and finally dehydrogenation to form aromatics. These results pave the way for processes that utilize ZSM-5 in the presence of water to convert hydrocarbons present in algae, used oils, food waste and other feeds into aromatic compounds.